Diarrhea, Weight Loss, and an Elevated Gastrin: A Case Report - Ryan G. Alexander; John C. Cheville; Geoffrey B. Thompson; Glenn L. Alexander (Case Reports in Gastroenterology)
Introduction: Hypergastrinemia in a patient with refractory reflux, steatorrhea, or peptic ulcer disease with a gastric pH <4 is concerning for Zollinger-Ellison syndrome (ZES), but antral G-cell hyperplasia can also present in this manner and is distinguished from ZES based on negative radiographic studies and secretory stimulation testing with a typical gastrin response to a standardized test meal. Case Presentation: A 51-year-old female with a history of a Nissen fundoplication for refractory reflux presented with a 3-month history of heartburn, diarrhea, and 55-pound weight loss. Evaluation included negative upper and lower endoscopies with biopsies and negative MR enterography. A 48-h fecal fat study revealed 501 g of stool and 51 g of fat per 24 h. A serum gastrin level off PPI was elevated at 589 pg/mL with a gastric pH of 2 on gastric aspirate. An EUS, DOTATATE PET scan, and secretin stimulation test were negative for ZE. A standardized test meal with serial gastrin monitoring demonstrated an 8-fold increase in serum gastrin. Open abdominal exploration and intraoperative ultrasound showed no evidence of a gastrinoma and an antrectomy and Billroth II anastomosis was performed in treatment of G-cell hyperplasia. Pathology demonstrated a moderately increased G-cell population. Postoperatively, her hypergastrinemia and steatorrhea resolved and she regained 60 pounds. Conclusion: Antral G-cell hyperplasia should be considered in patients with symptoms suggestive of gastrinoma with negative secretin stimulation testing and imaging studies. A standardized test meal demonstrates a substantial increase in serum gastrin levels and antrectomy is the treatment of choice for refractory symptoms.